Method for manufacturing polymer alloy
By using an aromatic thermoplastic resin matrix with dispersed organic fine particles and avoiding high shear processing, the polymer alloy achieves high transparency and resistance properties while preventing resin deterioration, addressing the limitations of conventional methods.
Patent Information
- Application Number
- JP2021104805
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-24
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-06-24
AI Technical Summary
Conventional melt kneading methods for producing polymer alloys, such as those involving polycarbonate and polymethyl methacrylate, suffer from resin deterioration due to high shear forces, resulting in a yellowish color tone and compromised properties like transparency, heat resistance, and impact resistance.
A polymer alloy is created using a matrix resin of aromatic thermoplastic resin and organic fine particles with diameters of 0.1 μm or less, which are dispersed within the matrix resin. This combination is processed without high shear forces, preventing resin deterioration and maintaining high transparency and resistance properties.
The resulting polymer alloy exhibits high transparency, suppressed resin deterioration, and enhanced heat resistance and impact resistance, while maintaining a color tone with yellowness of 50 or less, making it suitable for applications in transparent components.
Smart Images

Figure 0007655113000002 
Figure 0007655113000003 
Figure 0007655113000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer alloy, a method for producing the same, and a transparent part. [Background technology]
[0002] For example, transparent parts such as lenses, head-up display screens, and meter panels are required to be colorless and transparent, have small birefringence, and have excellent scratch resistance, weather resistance, heat resistance, and impact resistance. However, conventional transparent resins have a problem in that it is difficult to satisfy all of these characteristics. For example, polycarbonate resins, which are well known as transparent resins, are excellent in transparency, heat resistance, and impact resistance, but it is difficult to improve scratch resistance and weather resistance, and birefringence is likely to increase. In addition, for example, methacrylic resins are excellent in transparency, scratch resistance, weather resistance, and the like, but it is difficult to improve heat resistance and impact resistance.
[0003] Meanwhile, a technique has been proposed for obtaining a polymer alloy that combines the advantages of each polymer by mixing multiple types of polymers. For example, Patent Document 1 describes a melt-kneading method in which a resin consisting of 97-60% by weight of polycarbonate (PC) and 3-40% by weight of polymethyl methacrylate (PMMA) is blended using a micro-type high-shear molding machine. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-196196 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the melt-kneading method of Patent Document 1, two types of resins are kneaded by applying high shear force to reduce the size of the dispersed phase of polymethyl methacrylate in polycarbonate, thereby obtaining a transparent polymer alloy. However, the melt-kneading method of Patent Document 1 has a problem that the polycarbonate and polymethyl methacrylate are deteriorated by high shear during kneading, and tend to have a yellowish color.
[0006] The present invention has been made in consideration of such problems, and aims to provide a highly transparent polymer alloy in which deterioration of the resin contained in the polymer alloy is suppressed, a manufacturing method thereof, and a transparent part. [Means for solving the problem]
[0007] One aspect of the present invention reference The present invention relates to a matrix resin (11) made of an aromatic thermoplastic resin, The matrix resin is made of an organic resin, and organic fine particles (12) having a diameter of 0.1 μm or less are dispersed in the matrix resin. The polymer alloy (1) has a yellowness index of 50 or less when molded into a plate having a thickness of 2 mm.
[0008] One aspect of the present invention is a method for producing the polymer alloy of the above aspect, comprising the steps of: The matrix resin and a monomer capable of forming a (meth)acrylic resin are kneaded and heated to make the monomer compatible with the matrix resin and polymerize the monomer, thereby forming the organic fine particles in the matrix resin. , a method for producing a polymer alloy.
[0009] Further aspects of the present invention reference An embodiment of the present invention is a transparent part made of the polymer alloy of the above embodiment. Effect of the Invention
[0010] The matrix resin (11) of the polymer alloy (1) is an aromatic thermoplastic resin having excellent transparency, heat resistance, and impact resistance. By dispersing organic fine particles (12) made of an organic resin and having a diameter of 0.1 μm or less in this matrix resin, the polymer alloy can be given the properties of organic fine particles. In addition, the polymer alloy has a color tone whose yellowness falls within the specific range. In such a polymer alloy, deterioration of the organic resin constituting the matrix resin and the organic fine particles is suppressed.
[0011] In the manufacturing method of the above embodiment, the polymerizable organic compound is dissolved in the matrix resin, and then the polymerizable organic compound is polymerized in the matrix resin. As the polymerization reaction of the polymerizable organic compound in the matrix resin progresses and the molecular weight increases, the compatibility with the matrix resin decreases. When the polymerization reaction further progresses, organic fine particles having a diameter of 0.1 μm or less are spontaneously formed in the matrix resin due to spinodal decomposition.
[0012] Furthermore, in the above-mentioned manufacturing method, since it is not necessary to apply high shear to the matrix resin and the polymerizable organic compound when polymerizing the polymerizable organic compound, it is possible to avoid exposing the matrix resin and the polymerizable organic compound to extremely high temperatures during the manufacturing process of the polymer alloy. As a result, it is possible to suppress yellowing of the polymer alloy due to thermal degradation. Therefore, according to the above-mentioned manufacturing method, it is possible to easily obtain a polymer alloy having high transparency.
[0013] Furthermore, the transparent part of the above embodiment is made of the polymer alloy and therefore has high transparency.
[0014] As described above, according to the above-mentioned aspect, deterioration of the resin contained in the polymer alloy is suppressed, and it is possible to provide a highly transparent polymer alloy, a manufacturing method thereof, and a transparent part. In addition, the symbols in parentheses described in the claims and the means for solving the problems indicate a correspondence with the specific means described in the embodiments described below, and do not limit the technical scope of the present invention. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a cross-sectional view showing a main part of a polymer alloy according to a first embodiment. [Diagram 2] FIG. 2 is a partial cross-sectional view showing an example of a transparent part according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] (Embodiment 1) An embodiment of the polymer alloy 1 and its manufacturing method will be described with reference to Fig. 1. As shown in Fig. 1, the polymer alloy 1 has a matrix resin 11 made of an aromatic thermoplastic resin, and organic fine particles 12 made of an organic resin and having a diameter of 0.1 µm or less dispersed in the matrix resin 11. The polymer alloy 1 has a color tone that exhibits a yellowness index of 50 or less when molded into a plate having a thickness of 2 mm.
[0017] The matrix resin 11 in the polymer alloy 1 is an aromatic thermoplastic resin. As the aromatic thermoplastic resin, a transparent thermoplastic resin containing an aromatic ring in the molecular structure can be used. More specifically, examples of the aromatic thermoplastic resin include aromatic polycarbonate resin, polystyrene resin, polyamide-imide resin, polyetherimide resin, polyethersulfone resin, polyethylene naphthalate resin, etc.
[0018] The aromatic polycarbonate resin contains one or more types of structural units and carbonate bonds, and the structural units are bonded to each other via carbonate bonds. The aromatic polycarbonate resin also contains one or more types of structural units that contain an aromatic ring.
[0019] Examples of aromatic polycarbonates include bisphenol A polycarbonate resins containing structural units derived from bisphenol A, and special bisphenol polycarbonate resins containing structural units derived from bisphenols other than bisphenol A. Examples of bisphenol A polycarbonate resins that can be used include commercially available products such as "Iupilon (registered trademark) S-2000" manufactured by Mitsubishi Engineering Plastics Corporation, and "Panlite (registered trademark) 1255Y" and "Panlite (registered trademark) L-1255Z100M" manufactured by Teijin Limited. Examples of special bisphenol polycarbonate resins that can be used include commercially available products such as "Iupizeta (registered trademark) EP4000" and "Iupizeta EP5000" manufactured by Mitsubishi Gas Chemical Company, Inc.
[0020] The polystyrene resin contains structural units derived from styrene and / or a styrene derivative. As the polystyrene resin, for example, commercially available products such as "DicStyrene (registered trademark) GPPS CR-3500" manufactured by DIC Corporation and "Toyo Styrol (registered trademark) GP G320C" manufactured by Toyo Styrene Co., Ltd. can be used.
[0021] The polyamide-imide resin contains one or more structural units, amide bonds and imide bonds, and the structural units are bonded to each other via amide bonds or imide bonds. The polyamide-imide resin also contains one or more structural units containing an aromatic ring. As the polyamide-imide resin, for example, commercially available products such as "Viromax (registered trademark) HR-15ET" manufactured by Toyobo Co., Ltd. and "Torlon (registered trademark) 4203L" manufactured by Solvay Specialty Polymers Japan Co., Ltd. can be used.
[0022] The polyetherimide resin contains one or more structural units, ether bonds and imide bonds, and the structural units are bonded to each other via ether bonds or imide bonds. The polyetherimide resin also contains one or more structural units containing an aromatic ring. As the polyetherimide resin, for example, commercially available products such as "ULTEM (registered trademark) 1000" and "ULTEM 1010" manufactured by SHPP Japan Co., Ltd. can be used.
[0023] The polyethersulfone resin contains an aromatic ring, an ether bond, and a sulfone group (-SO2-), and the aromatic ring is bonded via an ether bond or a sulfone group. As the polyethersulfone resin, for example, commercially available products such as "Sumikaexcel (registered trademark) 4100G" manufactured by Sumitomo Chemical Co., Ltd. and "Veradel (registered trademark) 3600" manufactured by Solvay Specialty Polymers Japan Co., Ltd. can be used.
[0024] The polyethylene naphthalate resin contains one or more types of structural units and ester bonds, and the structural units are bonded to each other via ester bonds. The polyethylene naphthalate resin also contains one or more types of structural units containing a naphthalene ring. As the polyethylene naphthalate resin, for example, commercially available products such as "Teonex (registered trademark) TN8050SC" and "Teonex TN8065S" manufactured by Teijin Limited can be used.
[0025] The matrix resin 11 in the polymer alloy 1 is preferably an aromatic polycarbonate resin. Among aromatic thermoplastic resins, aromatic polycarbonate resins are less colored and have excellent transparency and heat resistance. Therefore, by using an aromatic polycarbonate resin as the matrix resin 11, the coloring of the polymer alloy 1 can be reduced, the transparency can be improved, and the heat resistance can be improved. In addition, aromatic polycarbonate resins are also suitable in that they are easily available. Furthermore, by dispersing organic fine particles 12 in the matrix resin 11 made of an aromatic polycarbonate resin, the phase difference of the polymer alloy 1 can be easily reduced. From these viewpoints, it is more preferable to use a bisphenol A type polycarbonate resin as the matrix resin 11 among aromatic bisphenol resins.
[0026] If necessary, additives such as an antioxidant, an ultraviolet absorbing agent, a hydrophilizing agent, etc. may be contained in the matrix resin 11. The content of the additives can be appropriately set within the range of, for example, 10 parts by mass or less per 100 parts by mass of the matrix resin 11.
[0027] Organic fine particles 12 made of an organic resin and having a diameter of 0.1 μm or less are dispersed in the matrix resin 11. By making the diameter of the organic fine particles 12 in the matrix resin 11 0.1 μm or less, the polymer alloy 1 can be given the characteristics of an organic resin without impairing the transparency of the entire polymer alloy 1. If the matrix resin 11 contains an excessively large number of organic fine particles 12 having a diameter exceeding 0.1 μm, the polymer alloy 1 may become easily cloudy. From the viewpoint of further increasing the transparency of the polymer alloy 1, the diameter of the organic fine particles 12 is preferably 0.08 μm or less, and more preferably 0.06 μm or less.
[0028] The diameter of the organic fine particles 12 in the polymer alloy 1 is the value of the circle-equivalent diameter of the organic fine particles 12 present within the field of view when the cross section of the polymer alloy 1 is observed by an electron microscope. The field of view area and observation position in the electron microscope observation may be appropriately set so that the number of organic fine particles 12 for which the circle-equivalent diameter is measured is, for example, 100 or more.
[0029] There is no particular lower limit to the diameter of the organic fine particles 12 in the polymer alloy 1. When the polymer alloy 1 is produced by the manufacturing method described below, the lower limit of the diameter of the organic fine particles 12 in the polymer alloy 1 is, for example, about 0.0001 μm to 0.0003 μm.
[0030] The content of the organic fine particles 12 in the polymer alloy 1 can be appropriately set from a range of, for example, 1 part by mass or more and 40 parts by mass or less with respect to 100 parts by mass of the matrix resin 11 and the organic fine particles 12 in total. By setting the content of the organic fine particles 12 to preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more with respect to 100 parts by mass of the matrix resin 11 and the organic fine particles 12 in total, the function of the organic resin constituting the organic fine particles 12 can be more reliably imparted to the polymer alloy 1. In addition, by setting the content of the organic fine particles 12 to preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less with respect to 100 parts by mass of the matrix resin 11 and the organic fine particles 12 in total, the function of the organic resin can be imparted to the polymer alloy 1 without impairing the transparency of the polymer alloy 1.
[0031] In the organic resin constituting the organic fine particles 12, one or more types of monomers are polymerized. (Meth)acrylic resinThe (meth)acrylic resin constituting the organic fine particles 12 may contain structural units derived from, for example, monofunctional (meth)acrylate monomers having one (meth)acryloyl group in the molecule, such as isobornyl methacrylate and 2-phenoxyethyl methacrylate, bifunctional (meth)acrylate monomers having two (meth)acryloyl groups in the molecule, such as neopentyl glycol dimethacrylate, 1,3-butylene diol dimethacrylate and ethoxylated bisphenol A dimethacrylate, and tetrafunctional (meth)acrylate monomers having four (meth)acryloyl groups in the molecule, such as pentaerythritol tetraacrylate and ditrimethylolpropane tetraacrylate.
[0032] An epoxy resin may be used as the organic resin when it is desired to impart adhesiveness and weather resistance to the polymer alloy 1. Examples of epoxy resins used in the organic fine particles 12 include bisphenol-type epoxy resins such as bisphenol A-type epoxy resins and bisphenol F-type epoxy resins, glycidylamine-type polyfunctional epoxy resins using polyfunctional glycidylamine as a curing agent, epoxy resins having flexible skeletons such as urethane-modified epoxy resins and rubber-modified epoxy resins, aliphatic epoxy resins having structural units derived from aliphatic alcohols such as ethylene glycol and glycerin, and alicyclic epoxy resins.
[0033] The polymer alloy 1 has a color tone that exhibits a yellowness of 50 or less when molded into a plate having a thickness of 2 mm. The yellowness of the polymer alloy 1 exhibits a large value when the matrix resin 11 is deteriorated. In the polymer alloy 1 having a yellowness within the specific range, deterioration of the organic resin constituting the matrix resin 11 and the organic fine particles 12 is sufficiently suppressed. In addition, by setting the yellowness of the polymer alloy 1 to the specific range, the color tone of the polymer alloy 1 can be made close to colorless. From this viewpoint, the yellowness of the polymer alloy 1 is preferably 40 or less, more preferably 30 or less, even more preferably 25 or less, and particularly preferably 20 or less.
[0034] The yellowness of the polymer alloy is a value measured by a method in accordance with JIS K7373:2006.
[0035] It is preferable that the polymer alloy 1 has a property that the transmittance at a wavelength of 600 nm is 50% or more when molded into a plate having a thickness of 2 mm. The polymer alloy 1 having such a property is suitable for transparent parts. From this viewpoint, it is more preferable that the polymer alloy 1 has a property that the transmittance at a wavelength of 600 nm is 55% or more when molded into a plate having a thickness of 2 mm, and it is even more preferable that the polymer alloy 1 has a property that the transmittance at a wavelength of 600 nm is 55% or more, and it is even more preferable that the polymer alloy 1 has a property that the transmittance is 60% or more when molded into a plate having a thickness of 2 mm.
[0036] In preparing the polymer alloy 1, first, a polymerizable organic compound capable of forming the organic resin is dissolved in the matrix resin 11. Next, the polymerizable organic compound in the matrix resin 11 is polymerized to form organic fine particles 12 in the matrix resin 11 . In this manner, polymer alloy 1 can be obtained.
[0037] In the above-mentioned production method, the method for dissolving the matrix resin 11 and the polymerizable organic compound is not particularly limited, and various methods can be adopted. For example, the matrix resin 11 and the polymerizable organic compound can be dissolved in the matrix resin 11 by feeding the matrix resin 11 and the polymerizable organic compound into an extrusion device or a kneader and kneading the matrix resin 11 and the polymerizable organic compound in the device.
[0038] In the manufacturing method, if necessary, a step of mixing additives, a polymerization catalyst for polymerizing the polymerizable organic compound, and the like with the matrix resin 11 may be performed. The work of mixing additives, polymerization catalyst, and the like with the matrix resin 11 may be performed at any time before the step of polymerizing the polymerizable organic compound. That is, for example, the matrix resin 11 may be mixed with additives, and then the polymerizable organic compound may be dissolved in the matrix resin 11, or the matrix resin 11 may be mixed with additives, and then the polymerizable organic compound may be dissolved in the matrix resin 11. In addition, for example, the polymerizable organic compound and additives, and the like may be mixed in advance, and then the mixture and the matrix resin 11 may be mixed, so that the step of mixing the matrix resin 11 with additives, and the step of dissolving the polymerizable organic compound in the matrix resin 11 can be performed as a single step.
[0039] In the process of making the matrix resin 11 and the polymerizable organic compound compatible and in the process of mixing the matrix resin 11 with additives, etc., the matrix resin 11 may be heated and softened as necessary. The heating temperature of the matrix resin 11 may be appropriately set depending on the material of the matrix resin 11.
[0040] For example, when the matrix resin 11 contains both a polymerizable organic compound and a polymerization catalyst, the heating temperature of the matrix resin 11 can be made as low as possible to suppress the polymerization reaction of the polymerizable organic compound during the mixing operation while sufficiently dissolving the matrix resin 11 and the polymerizable organic compound. As a result, the formation of coarse organic particles 12 in the finally obtained polymer alloy 1 can be more effectively suppressed. More specifically, when the matrix resin 11 contains both a polymerizable organic compound and a polymerization catalyst, the heating temperature of the matrix resin 11 is preferably 150°C or higher and 280°C or lower, more preferably 170°C or higher and 250°C or lower, and even more preferably 180°C or higher and 230°C or lower.
[0041] In the manufacturing method, after the polymerizable organic compound is dissolved in the matrix resin 11, the polymerizable organic compound in the matrix resin 11 is polymerized. When the polymerization reaction of the polymerizable organic compound progresses in the matrix resin 11 and the degree of polymerization of the organic resin increases, the compatibility between the organic resin and the matrix resin 11 decreases. When the organic resin becomes unable to dissolve in the matrix resin 11, organic fine particles 12 are spontaneously formed in the matrix resin 11 by spinodal decomposition. As a result, the polymer alloy 1 can be obtained.
[0042] The method of polymerizing the polymerizable organic compound in the matrix resin 11 is not particularly limited, and a method according to the aspect of the polymerization reaction can be adopted. For example, when the polymerization reaction is accelerated by heat, the matrix resin 11 in which the polymerizable organic compound is dissolved may be heated to polymerize the polymerizable organic compound in the matrix resin 11. In addition, the polymerizable organic compound may be polymerized in the matrix resin 11 by heating a mixture of the matrix resin 11 and the polymerizable organic compound while kneading the mixture in an extrusion device or a kneader. When the polymerizable organic compound is polymerized using an extrusion device or a kneader, the polymerizable organic compound may be polymerized using the same device after the polymerizable organic compound is dissolved in the matrix resin 11, or the polymerizable organic compound may be polymerized using a device other than the device used for dissolving the polymerizable organic compound in the matrix resin 11.
[0043] The shape of the polymer alloy 1 obtained by the above-mentioned manufacturing method is not particularly limited. For example, a strand of the polymer alloy 1 is produced using an extrusion device, and then the strand is cut using a pelletizer to obtain pellets of the polymer alloy 1. The pellets of the polymer alloy 1 thus obtained can be molded using a method such as injection molding or compression molding to obtain a transparent part having a desired shape.
[0044] Also, for example, after polymerizing the polymerizable organic compound in the matrix resin 11 in an injection molding device, the polymer alloy 1 in a molten state can be injection molded to obtain a transparent part having a desired shape.
[0045] (Embodiment 2) In this embodiment, an example of a transparent part made of the polymer alloy will be described with reference to Fig. 2. Among the symbols used in the second and subsequent embodiments, the same symbols as those used in the previous embodiments represent the same components, etc. as those in the previous embodiments, unless otherwise specified.
[0046] The polymer alloy 1 of the first embodiment can be applied to various transparent parts 2. The transparent part 2 may be, for example, a screen 21 of a head-up display 3 as shown in FIG. 2. The head-up display 3 shown in FIG. 3 has a circuit board 31, a light source 32 held by the circuit board 31, a magnifying mirror 33 arranged on the optical path L of the light generated from the light source 32, a stay 34 holding the magnifying mirror 33, and a screen 21 arranged on the optical path L of the light reflected by the magnifying mirror 33. An adhesive 35 is interposed between the circuit board 31 and the light source 32, and between the magnifying mirror 33 and the stay 34, and these components are joined via the adhesive 35.
[0047] The polymer alloy 1 of the first embodiment can be applied to various transparent parts 2 such as lenses and meter panels in addition to the screen 21 for the head-up display 3.
[0048] The refractive index of the transparent part made of the polymer alloy 1 may be anisotropic, and in this case, a phase difference may occur in the light passing through the transparent part. The phase difference is expressed as the product of the birefringence of the transparent part and the distance the light passes through the transparent part. A transparent part having a phase difference changes the polarization state of the light passing through the transparent part, and therefore may cause problems such as a decrease in brightness and the occurrence of rainbow unevenness, for example, when the light passing through the transparent part further passes through a polarizer. In order to avoid these problems, the smaller the phase difference of the transparent part, the more preferable it is.
[0049] (Experimental Example) In this example, a more specific example of the configuration of the polymer alloy 1 according to the embodiment 1 will be described together with a manufacturing method. The matrix resin, polymerizable organic compound, and polymerization catalyst used in this example are as follows.
[0050] Polymer P1: Aromatic polycarbonate resin (Teijin Limited "Panlite 1255Y") Polymer P2: Aromatic polycarbonate resin (Teijin Limited "Panlite 1255") Polymer P3: Acrylic resin ("ACRYPET (registered trademark) VHS-001" manufactured by Mitsubishi Chemical Corporation)
[0051] Monomer M1: Isobornyl methacrylate Monomer M2: Neopentyl glycol dimethacrylate Monomer M3: Pentaerythritol tetraacrylate Monomer M4: Ethoxylated bisphenol A dimethacrylate Monomer M5: Epoxy compound ("jER (registered trademark) 828" manufactured by Mitsubishi Chemical Corporation) Monomer M6: Epoxy compound ("jER 806" manufactured by Mitsubishi Chemical Corporation)
[0052] Polymerization catalyst C1: Di-t-amyl peroxide Polymerization catalyst C2: Epoxy resin curing agent ("jER Cure (registered trademark) DICY15" manufactured by Mitsubishi Chemical Corporation)
[0053] In producing the polymer alloy 1 of this example, polymer P1 and polymer P2, which had been dried in advance by keeping them at a temperature of 80°C for 12 hours in a vacuum, were used as the matrix resin 11. In addition to preparing the matrix resin 11, polymerizable organic compounds (monomers M1 to M6) and a polymerization catalyst were mixed in the mass ratio shown in Table 1 to produce a mixture of the polymerizable organic compounds and the polymerization catalyst.
[0054] Next, either polymer P1 or polymer P2 was put into a kneader ("Labo Plastomill (registered trademark)" manufactured by Toyo Seiki Co., Ltd.) as a matrix resin 11, and the matrix resin 11 was kneaded while being heated at a temperature of 200 ° C., thereby melting the matrix resin 11. Next, a mixture of a polymerizable organic compound and a polymerization catalyst was added to the matrix resin 11 in the kneader in the mass ratio shown in Table 1. Then, the contents of the kneader were kneaded at a temperature of 200 ° C. for 7 minutes, thereby dissolving the polymerizable organic compound in the matrix resin 11 and polymerizing the polymerizable organic compound at the same time. The screw rotation speed in the kneader was set to 150 rpm. As a result of the above, polymer alloy 1 (test material S1 to test material S9) shown in Table 1 was obtained.
[0055] Test materials R1 to R4 shown in Table 1 are test materials for comparison with test materials S1 to S9. Test material R1 was prepared in the same manner as test materials S1 to S9, except that polymer P1 and polymer P3, which had been dried in advance by holding them at a temperature of 80° C. for 12 hours in a vacuum, were mixed in the mass ratio shown in Table 1, and kneaded using a kneader.
[0056] In preparing test material R2, the polymers were mixed in the mass ratio shown in Table 1. Polymer P1 and polymer P3 were put into a micro-type high shear molding machine and melted in the machine, and then high shear force was applied to disperse polymer P3 in polymer P1. More specifically, the temperature of polymer P1 and polymer P3 in the machine was 250°C, and the screw rotation speed of the machine was 3000 rpm. The residence time of polymer P1 and polymer P3 in the machine was about 1 to 2 minutes.
[0057] The properties of the test materials S1 to S9 and R1 to R4 obtained as described above were evaluated by the following methods.
[0058] [Diameter of organic particles] After cutting the test material at an appropriate cross section, the cross-sectional morphology was observed using an electron microscope. The equivalent circle diameter of organic particles present within a visual field of 0.4 μm vertical and 0.4 μm horizontal was calculated, and this value was taken as the diameter of the organic particles. In the "Diameter of organic particles" column of Table 1, the symbol "A+" was entered when the maximum diameter of the organic particles was 0.05 μm or less, the symbol "A" was entered when it was more than 0.05 μm and less than 0.10 μm, and the symbol "B" was entered when it was more than 0.10 μm.
[0059] [Transparency] Each test material was molded into a plate of 100 mm length, 100 mm width, and 2 mm thickness by heat press molding to prepare a test piece for transparency evaluation. The transmittance of the test piece at a wavelength of 600 nm was measured using an ultraviolet-visible near-infrared spectrophotometer ("V-550" manufactured by JASCO Corporation). In the "Transparency" column of Table 1, the symbol "A+" was written when the transmittance of the test piece at a wavelength of 600 nm was 55% or more, the symbol "A" was written when the transmittance was 50% or more and less than 55%, and the symbol "B" was written when the transmittance was less than 50%. In the transparency evaluation, the symbols "A+" and "A" in which the transmittance of the test piece at a wavelength of 600 nm was 50% or more were judged to have high transparency and to pass.
[0060] [Yellowness] Each test material was molded into a plate of 100 mm length, 100 mm width, and 2 mm thickness by hot press molding to prepare a test piece for measuring yellowness. The yellowness of the test piece was measured by the method specified in JIS K7373:2006 using a near-infrared microspectrophotometer (Olympus Corporation "USPM-RU-WRD"). In the "yellowness" column of Table 1, the symbol "A+" was entered when the yellowness of the test piece was less than 40, the symbol "A" was entered when it was 40 to 50, and the symbol "B" was entered when it was more than 50. Note that for test material R3, the symbol "-" was entered in the same column because the test piece was opaque and the yellowness could not be measured. In the evaluation of transparency, the cases of the symbols "A+" and "A" where the yellowness of the test piece was 50% or less were judged to be passed because the yellowing of the polymer alloy 1 was small.
[0061] [Phase difference] Each test material was molded into a plate of 100 mm length, 100 mm width, and 2 mm thickness by hot press molding to prepare a test piece for measuring retardation. The retardation of the test piece was measured using a two-dimensional birefringence evaluation system (Photonic Lattice Co., Ltd.'s "WPA-200"). In the "Retardation" column of Table 1, the symbol "A+" was entered when the retardation of the test piece was less than 20 nm, the symbol "A" was entered when it was 20 nm or more and 30 nm or less, and the symbol "B" was entered when it was more than 30 nm. Note that for test material R3, the symbol "-" was entered in the same column because the test piece was opaque and the retardation could not be measured.
[0062] [Heat resistance] Each test material was molded into a plate of 100 mm length, 100 mm width, and 2 mm thickness by hot press molding, and then the plate was cut to obtain heat resistance measurement specimens of 30 mm length, 10 mm width, and 2 mm thickness. Using a dynamic viscoelasticity device (TA Instruments Japan, Inc., "RSA G2"), the tan δ, that is, the ratio of the loss modulus E'' to the storage modulus E', was measured at various temperatures while increasing the temperature of the test specimen. The peak temperature of tan δ of the matrix resin contained in the test specimen was determined as the glass transition temperature of the matrix resin.
[0063] In the "Heat resistance" column of Table 1, the glass transition temperature of the matrix resin contained in the test piece is indicated as "A+" if it is 150°C or higher, "A" if it is 145°C or higher but less than 150°C, and "B" if it is less than 145°C.
[0064] [Table 1]
[0065] As shown in Table 1, the test materials S1 to S9 each have a matrix resin 11 made of an aromatic thermoplastic resin, and organic fine particles 12 made of an organic resin and having a diameter of 0.1 μm or less dispersed in the matrix resin 11. Furthermore, the test materials S1 to S9 each have a color tone that exhibits a yellowness index of 50 or less when molded into a plate having a thickness of 2 mm. These test materials have high transparency, and deterioration of the organic resin constituting the matrix resin 11 and the organic fine particles 12 during the manufacturing process is suppressed. Furthermore, the test materials S1 to S9 can impart the function of the organic resin constituting the organic fine particles 12 to the polymer alloy 1 while maintaining transparency.
[0066] On the other hand, the test material R1 is made of an aromatic polycarbonate resin, and the aromatic polycarbonate does not contain organic fine particles 12. Therefore, the function of the organic resin constituting the organic fine particles 12 is not imparted to the test material R1, and the phase difference is larger than those of the test materials S1 to S9.
[0067] Test material R2 is made of methacrylic resin and does not contain organic fine particles 12. Therefore, test material R2 is inferior in heat resistance to test materials S1 to S9, which use aromatic polycarbonate resin as the matrix resin.
[0068] In the test material R3, aromatic polycarbonate resin and methacrylic resin were kneaded by a general method, so that the diameter of the methacrylic resin in the aromatic polycarbonate resin was large. Therefore, the transparency of the test material R3 was lower than that of the test materials S1 to S9.
[0069] In the test material R4, the aromatic polycarbonate resin and the methacrylic resin were kneaded by applying a high shear force, and the deterioration of the aromatic polycarbonate resin progressed during the manufacturing process. Therefore, the yellowness of the test material R4 was higher than that of the test materials S1 to S9.
[0070] The present invention is not limited to the above-described embodiments, and can be applied to various embodiments without departing from the gist of the present invention. [Explanation of symbols]
[0071] 1 Polymer alloy 11 Matrix Resin 12 Organic fine particles
Claims
1. A matrix resin (11) made of an aromatic polycarbonate resin; and (12) organic fine particles having a diameter of 0.1 μm or less, which are made of a (meth)acrylic resin and are dispersed in the matrix resin, A method for producing a polymer alloy (1), which has a color tone showing a yellowness index of 50 or less when molded into a plate having a thickness of 2 mm, comprising: A method for producing a polymer alloy, comprising heating the matrix resin and a monomer capable of forming a (meth)acrylic resin while kneading them together to dissolve the monomer in the matrix resin and polymerize the monomer, thereby forming the organic fine particles in the matrix resin.
2. The method for producing a polymer alloy according to claim 1, wherein the content of the organic fine particles is 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the total of the matrix resin and the organic fine particles.
Citation Information
Patent Citations
Thermoplastic resin composition
JP1991047851A
Flame-retardant resin composition
JP1995090165A
Polycarbonate / Polyolefin resin composition and molded product, its production
JP1996157664A
Thermoplastic resin composition
JP1998310707A
Thermoplastic resin composition
JP2000290486A